Educação financeira crítica: uma abordagem associada à aprendizagem baseada em projetos - Boito, Paula (2025)
Participating in the formation of a better society is a challenge to which school must prepare itself, as its students are still in the process of developing skills expected from 21st century citizens, including autonomy and protagonism. A pedagogical resource to promote the development of these skills are active learning methodologies, among which project-based learning (PBL), which has as its characteristic the resolution of more complex problems, divided into stages, on which students, in their teams, they need to research, create hypotheses, build and analyze data and create a product as the completion of the project. In this context, the present research starts from a project using critical financial education as a theme, which is part of the Economy, a transversal contemporary theme according to BNCC (Brazil, 2018) and, as such, is of interest to the whole society. As a research problem, it is intended to associate the use of PBL to the competencies explained in BNCC, especially those that refer to the area of mathematics. As a central question, we seek how it is possible to implement PBL in high school classes, in order to contribute to the development of students as protagonists in their financial decisions? The main objective of the work is to implement the active methodology of projectbased learning in a regular high school class, using as in order to provide the development of autonomy and protagonism in relation to personal finances. For this, an educational product in e-book format was developed, with the title Critical financial education practices in high school, based on project-based learning. The application of this educational product was carried out with high school students in a school in Passo Fundo, RS, in 2024. The research carried out had a qualitative nature, because it sought to understand the process involved and to what extent it affected the students. It was an action research, having as its theme a social issue, whose participation directly involves the researcher and her class of students. For the production of data, individual questionnaires and also by teams for students, written assessments of scientific knowledge and the researcher’s logbook were used, as well as transcriptions of dialogues that took place in the classroom. The data analysis was done through the categories autonomy and protagonism. It was observed a good engagement of the students regarding the application of PBL, emphasizing the participation in all stages of the project, starring and anticipating various situations during the activities. As a result, there is evidence that students have developed more autonomy, taking part in situations through real problems and performing tasks that stimulated them to have initiative, to debate, becoming responsible for the construction of knowledge. It is noteworthy that the students showed interest in continuing to use the methodology in mathematics classes, by appropriating knowledge more dynamically through their own discoveries. The educational product linked to the thesis brings tips for each stage of PBL, from planning to evaluation. This material is free and available for download in the repository of the UPF Graduate Program in Science and Mathematics Education (https://www.upf.br/ppgecm) and on the Educapes Portal (http://educapes.capes.gov.br/handle/capes/1000989).